Knowledge attitude and practice of blood donation in Hail University - Alanazi, Manal Th.; Elagib, Halima; Aloufi, Haneen R.; Alshammari, Beshayer M.; Alanazi, Samiyah M.; Alharbi, Shaden F.; Alshamasy, Hadeel K.; Alrasheedi, Rawan N. (International Journal Of Community Medicine And Public Health, 2018)
Background: Medical students should be well educated about blood donation and its importance, and their knowledge reflects what will be transferred to the community. Thus, the aim of this study was to explore the knowledge, attitude, and practice of blood donations among medical students in Hail University. Methods: Three hundred medical students from 2nd to 6th grade participated in this self-administered questionnaire that included their demographic data, questions about their previous experience with blood donation, and questions about their knowledge and attitudes about blood donation. Results: Out of the 300 students (50 males and 50 females), among them about 88% of students knew their blood group. About 75% knew that infections can be transmitted through blood donation, especially HIV (90%), HBV (73%), HCV (71.3%), and malaria (48%). One third believed that the minimum hemoglobin level for blood donation is 12.5 g/L in men and 12 g/L in women. Negative attitudes towards blood donation included donation to relative request only (24%), paid donations (29.7%), and belief of probability to get infected (34%). Positive attitudes were addressed beliefs that donation saves lives (72%), donation is a moral activity (43%), and importance of disclosing real information before donation (46.3%). Males donated blood more than females (p<0.001), whilst females were more fearful of needles (p=0.001). Gender was significantly correlated with blood donation with an Odd's ratio of 0.28 (p<0.001). Conclusions: Knowledge, attitude, and practice of medical students about blood donation are highly variable among different grades and genders of students in Hail University.